Product of the Edge. Maâjoun or Hashish with Ambivalent Symbolism - Hadji, Khalid (E|C, 2025)
To achieve a certain stability, society produces its own alterity, which is expressed in conventional, officially accepted forms, or conversely, in excluded forms that nonetheless manage to persist on the margins of the community, unrecognised, yet tolerated. Within this framework lies Maâjoun, a marginal product of ambivalent nature: both licit and illicit, food and drug, used to create a convivial atmosphere or to induce intoxication, and consumed across different social classes. This ambiguity intensifies in the Moroccan-Islamic context, where the phenomenon, though not legally recognised, is also not explicitly prohibited, thereby generating a symbolic dilemma. Maâjoun is thus perceived both as a marginal narcotic and as a refined delicacy, consumed within selective ritual contexts. This paradoxical situation invites reflection on the semiotic nature of the phenomenon and raises the question of which epistemological stance to adopt to render this cultural “figure” more intelligible. This figure is a priori determined by the social representation from which it emerges, where the practice of Maâjoun and its accompanying social ethics are intimately tied to symbolic form. We must therefore ask a methodological question: what means should we use to define this semiotic “object” in terms of its constituents, in order to approach it as a “subject” of knowledge and assign it a status? To do this, we propose tackling the issue from three directions: firstly, by contextualising it to define the existence of forms and practices of marginality; then, by analysing the context and ritual of Maâjoun consumption; and finally, by addressing its cultural meaning and symbolic investment.